Pengembangan Fitur Website X-Camp dengan Pendekatan User-Centered Design : Studi Kasus PT XL Axiata - Endah, Ossy Dwi; Heningtyas, Yunda; Hermawan, Ghina Aramita; Kurniawan, Didik (Lambung Mangkurat University, 2023)
This article discusses the application of the User-Centered Design method in developing features on the X-Camp PT XL Axiata Tbk website. PT XL Axiata Tbk is a cellular telecommunications operator company in Indonesia. XL Axiata currently has a variety of main products and one of the products issued by XL Axiata is based on IoT which is supported by X-Camp. X-Camp is an innovation center built to accelerate the development of the IoT ecosystem in Indonesia. X-Camp has a website that was built using the CodeIgniter 3 framework. The CodeIgniter framework is a PHP framework with an MVC (Model, View, Controller) model so that it can be used to build dynamic web applications. The purpose of this research is to produce a feature and system that can be used by admins and users easily. The development in this research uses the User-Centered Design method. This research produces a form that can be used by users to join various activities organized by X-CAMP. In addition, features were also developed on the website administrator that can be used by the X-CAMP admin to manage the content that will be presented on the X-CAMP website.